Pembelajaran Bahasa Inggris Teks Prosedur Berbasis Fiqih Perawatan Jenazah - Basya, Dihliza (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The design of English learning in Islamic boarding school-based institutions must be tailored to meet the needs of students while aligning with Islamic values. One of the methods employed involves English for Specific Purposes (ESP), which incorporates content related to the jurisprudence of corpse care. This community service program seeks to enhance students' English language proficiency by utilizing procedural texts within a fiqh context, ensuring that students not only grasp linguistic structures but also acquire relevant religious insights. The methods of implementation encompass stages of preparation, training, and evaluation. Training activities emphasize the development of reading, listening, speaking, and writing skills through procedural text materials that detail the processes involved in corpse care. The findings of the activity indicated a notable enhancement in students' vocabulary mastery, comprehension of text structure, and presentation skills. Furthermore, participants expressed favorable reactions as the content examined aligned with their spiritual and social requirements. Consequently, incorporating ESP grounded in corpse jurisprudence into the study of procedural texts may serve as a framework for enhancing contextual English literacy within the Islamic boarding school setting.